Space and development: a non-hegemonic view - Giugliano, Rogério Gimenes (Ciência & Trópico, 2013)
ABSTRACTThe intensification of south-south cooperation imposes new challenges to the understanding of development. In contrast with hegemonic discourse and based on the on-going research about the IBSA Trilateral Dialog this text presents and discusses spatialized approach to development.KEYWORDS: Development. South-South. Hegemony. IBSA.Espaço e desenvolvimento: uma visão não hegemônicaRESUMOA intensificação da cooperação Sul-Sul impõe novos desafios para a compreensão do desenvolvimento. Em contraste com o discurso hegemônico e com base na investigação em curso sobre o Diálogo Trilateral do IBAS, este trabalho apresenta e discute uma abordagem espacializadas ao desenvolvimento.PALAVRAS-CHAVE: Desenvolvimento. Sul-Sul. Hegemonia. IBAS.